NAQD AL-TAHDÎTS FÎ RIWÂYAH LAYÂLÎ TURKISTAN LI NAJIB AL-KAELANI BINÂ’ ‘ALÂ WIJHAH NADZHAR THEODOR WIESENGRUND ADORNO - Masykur, Hasan Basri; Zuhdy, Halimi; Erwhintiana, Ifi; Al-Dakhiel, Muhammad Majed (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This study aimed to describe the patterns of modernization criticism, the factor emerging critics, and the impact of modernization in Layali Turkistan's novel according to Adorno's perspective. This study employed a descriptive qualitative approach methodology by obtaining the primary data from Layali Turkistan novel and gaining the secondary data from other references. The data were collected through reading and noting. Moreover, the writer employed triangulation to test the data validity. Meanwhile, Milles and Huberman's model was used to analyze the data. The writer revealed that: 1) The patterns of modernization critics in Layali Turkistan's novel are on modernization's behalf; in which Russian and Chinese have set aside their sense of humanity, such as tolerance and respect. 2) The emerging critics of modernization are religiosity, science, and technology development. 3) The impacts of modernization are humanity, morality, spiritual crisis, and natural resource ownership segregation.